Fixed Dose Botulinum toxin therapy for Blepharospasm - Saher Khalid, Muhammad Moin (Pakistan Journal of Ophthalmology, 2016)
Purpose: To find the efficacy of a fixed dose of Botulinum toxin A for the treatment of Blepharospasm. Study Design: Quasi experimental study. Place and Duration of study: Yaqin Vision Clinic, Lahore from (August 2010 – August 2015). Material and Methods: All patients of Blepharospasm treated with botulinum toxin included in the study were assessed on first visit for the presence of blepharospasm and graded into 4 patterns from mild to severe. Ocular examination was done to rule out any cause of secondary blepharospasm due to trichiasis or entropion. CT or MRI scan was performed to rule out any neurological cause of the disease. Injections were given at 7 periocular sites in a fixed dose. Follow up was done at 2 weeks, 6 weeks and 3 months. Results: There were 53 cases of blepharospasm, 27 males and 26 females, which were treated with botulinum toxin. Average age of the patients was 55.3 +/- 8.4. Out of these only 34 patients (64%) had regular injections while 19 patients (36%) had only one injection and did not turn up for further treatment. Average number of injections given to each patient was 5.5 +/- 4.7. The average duration of relief of symptoms was 3.1 +/- 1 month with 25 units of Botulinum toxin at 7 periocular sites on each side. Relief of symptoms started after 3.6 +/- 1.8 days in most of the patients. Pre-op 23 patients had moderate and 11 had severe spasms. Average spasms at 1 month post injection were slight to mild with better response in patient with moderate pre-op spasms. One patient each had post injection headache and drooping of lid after injection. Conclusion: Fixed dose therapy gives satisfactory results in patients with moderate blepharospasm. Key words: To Severe Botolinum Toxin, Blepharospasm, Injections.